2017
DOI: 10.1080/08927014.2017.1383983
|View full text |Cite
|
Sign up to set email alerts
|

Marine antifouling performance of polymer coatings incorporating zwitterions

Abstract: Zwitterionic materials display antifouling promise, but their potential in marine anti-biofouling is still largely unexplored. This study evaluates the effectiveness of incorporating small quantities (0-20% on a molar basis) of zwitterions as sulfobetaine methacrylate (SBMA) or carboxybetaine methacrylate (CBMA) into lauryl methacrylate-based coatings whose relatively hydrophobic nature encourages adhesion of the diatom Navicula incerta, a common microfouling organism responsible for the formation of 'slime'. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Similar observations were made previously for amphiphilic PEG block copolymers. [ 20,32,52 ] The good performance of amphiphilic zwitterionic polymers is in line with many results in literature showing high resistance against cell adhesion, [ 30 ] attachment of N. incertia , [ 29 ] and a good anti‐fouling performance against zoospores of U. linza . [ 53 ]…”
Section: Discussionsupporting
confidence: 72%
“…Similar observations were made previously for amphiphilic PEG block copolymers. [ 20,32,52 ] The good performance of amphiphilic zwitterionic polymers is in line with many results in literature showing high resistance against cell adhesion, [ 30 ] attachment of N. incertia , [ 29 ] and a good anti‐fouling performance against zoospores of U. linza . [ 53 ]…”
Section: Discussionsupporting
confidence: 72%
“…[213] It has also been suggested that incorporating of relatively small amount of zwitterions into polymer coatings could enhance fouling-release properties. [215,216] Recently, Knowles et al have chosen to investigate the antifouling behavior of coatings prepared from silica nanoparticles (SiNPs) of various sizes grafted with hydrophilic zwitterionic chemistries. The coatings demonstrated a high degree of nonspecific protein resistance: adsorption of bovine serum albumin and hydrophobin proteins were reduced by up to 91% and 94%, respectively.…”
Section: Zwitterionic Polymersmentioning
confidence: 99%
“…After 75 days the samples were removed and tested for biofilm release in a variable-speed hydrodynamic flow-cell (Politis et al 2009). The fouled microscope slides were installed in the flow cell and fully turbulent seawater was passed along the surfaces as described in the literature (Ventura et al 2017;Benschop et al 2018). The water velocity was incrementally increased from zero to 4.1 m s À1 (1.5, 2.1, 2.6, 3.1, 3.6 and 4.1 m s À1 ), while remaining constant at each speed for 1 min.…”
Section: Biofilm Growth and Release Testingmentioning
confidence: 99%